Therapeutic effects of noni fruit water extract and polysaccharide on oxidative stress and inflammation in mice under high-fat diet. Issue 1 (12th December 2019) - Yang, Xiaobing; Lin, Chunrui; Cai, Shuang; Li, Wenzhi; Tang, Jian; Wu, Xiaoyong
Abstract : This study aims to compare the therapeutic effects of noni fruit water extract (NFW) and noni fruit polysaccharide (NFP) on oxidative stress and inflammation in mice under high-fat diet. Abstract : This study aims to compare the therapeutic effects of noni fruit water extract (NFW) and noni fruit polysaccharide (NFP) on oxidative stress and inflammation in mice under high-fat diet. In this study, mice were induced to develop oxidative stress and inflammation through high-fat diet. Treatment was performed via the administration of NFW (10 mL per kg bw) and NFP (50, 100, and 200 mg per kg bw) for 4 weeks. The results indicated that the NFW and NFP reduced the body weight gain, liver relative weight, and abdominal fat relative weight of mice under high-fat diet. Moreover, the NFW and NFP reduced the liver malondialdehyde level and increased the liver trolox equivalent antioxidant capacity level. The NFP effectively increased the liver superoxide dismutase and glutathione peroxidase activities, and the administration of NFP at 100 and 200 mg per kg bw effectively increased the hepatic nuclear factor erythroid-2 related factor level, thus presenting improved antioxidant activity. The NFW and NFP restrained the elevation of tumor necrosis factor alpha, interleutin-6, and nitric oxide levels in the liver and serum. All NFP doses prominently decreased the hepatic nuclear factor kappa B level, and the NFP at 100 and 200 mg per kg bw presented high anti-inflammatory activity. These results suggested that the NFW and NFP alleviated oxidative stress and inflammation in mice under high-fat diet, and the NFP at 100 mg per kg bw had a better effect than NFW with a similar polysaccharide dosage, illustrating that NFP may be an important component in the NFW.